Feminist Critiques against Traditional Approaches to Security - Petrus Farneubun (Global Strategis, 2015)
Feminists claim that national security is a model of masculinity domination,which hardly disputes. This essay addresses feminists critique on notion ofconventional security and provides feminists own definition. It shows thatfeminists adopt comprehensive approach in relation to security. They tend todefine security in a broad term to accomodate contemporary issues. They alsopropose neutral concept of security to demonstrate that security is notexclusively men’s business.